The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1099/ijs.0.055079-0
|View full text |Cite
|
Sign up to set email alerts
|

Pyrinomonas methylaliphatogenes gen. nov., sp. nov., a novel group 4 thermophilic member of the phylum Acidobacteria from geothermal soils

Abstract: Pyrinomonas methylaliphatogenes gen. nov., sp. nov., a novel group 4 thermophilic member of the phylum Acidobacteria from geothermal soils An aerobic, thermophilic, moderately acidophilic non-spore-forming bacterium, strain K22 T , was isolated from geothermally heated soil at Mount Ngauruhoe, New Zealand. On the basis of 16S rRNA gene sequence similarity, K22 T was shown to belong to subdivision 4 of the phylum Acidobacteria and to be most closely related to 'Candidatus Chloracidobacterium thermophilum' (86 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 38 publications
(59 reference statements)
2
39
0
1
Order By: Relevance
“…Seven strains of bacteria belonging to Acidobacteria SD 4 were analyzed for their lipid compositions; five are species that have previously been characterized (Blastocatella fastidiosa [42], Pyrinomonas methylaliphatogenes [44], "Ca. Chloracidobacterium thermophilum" [41], Aridibacter famidurans, and Aridibacter kavangonensis [43]), and two are novel strains isolated from soils in Namibia (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven strains of bacteria belonging to Acidobacteria SD 4 were analyzed for their lipid compositions; five are species that have previously been characterized (Blastocatella fastidiosa [42], Pyrinomonas methylaliphatogenes [44], "Ca. Chloracidobacterium thermophilum" [41], Aridibacter famidurans, and Aridibacter kavangonensis [43]), and two are novel strains isolated from soils in Namibia (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Blastocatella fastidosa, an aerobic chemoorganoheterotroph (42), and two Aridibacter species (43) were isolated from semiarid savannah soils. The thermophile Pyrinomonas methylaliphatogenes was isolated from a geothermally heated soil and possesses a chemoheterotrophic and obligately aerobic metabolism (44). Molecular ecological studies based on 16S rRNA genes have indicated that, in wetlands, the most abundant Acidobacteria members fall in SD 1 and 3 (21), whereas in lakes SD 1, 6, and 7 thrive (45).…”
mentioning
confidence: 99%
“…The abundance of transporters specific for amino acids, polyamines and organocations seemed to be especially high in the genomes stemming from terrestrial strains (Supporting Information Table S6), suggesting their potential to not only use inorganic but also organic N sources via mineralization. Soils have been reported to contain varying types and amounts of free amino acids (Monreal and McGill, 1985;Kielland, 1994), which could serve as a source of N. Although select strains have been reported to grow on ammonia, nitrate, nitrite and/or amino acids (Eichorst, 2007;Koch et al, 2008;Dedysh et al, 2012;Crowe et al, 2014;Tank and Bryant, 2015b;Myers and King, 2016;Vieira et al, 2017;D. Trojan and S.A. Eichorst, unpublished data), a more detailed growth-based study is warranted, as previous work illustrated that while C. thermophilum B harboured putative genes for ammonium uptake, it was unable to grow solely on ammonium (Tank and Bryant, 2015b).…”
Section: Assimilatory Nitrogen Metabolism Nitrification and Nitrogenmentioning
confidence: 99%
“…Based on previous genomic and physiological investigations, many subdivision 1 and 3 strains have been described as versatile heterotrophs that grow optimally at low pH, produce copious amounts of extracellular material, harbour a low rRNA operon copy number suggesting an oligotrophic (more K-selected) lifestyle, and contain both low-specificity major facilitator superfamily and high-affinity ABC-type transporters (Ward et al, 2009;Rawat et al, 2012;Kielak et al, 2016). Some more striking physiologies such as iron reduction and/or fermentative growth (Liesack et al, 1994;Coates et al, 1999), phototrophy (Garcia Costas et al, 2012), along with the ability to grow under thermophilic conditions have been described in select strains from subdivision 4, 8, 10 and 23 (Izumi et al, 2012;Losey et al, 2013;Crowe et al, 2014;Stamps et al, 2014;Tank and Bryant, 2015a). Yet the vast majority of acidobacteria detected in soils based on culture dependent and independent approaches are members of subdivisions 1, 2, 3, 4, 5 and 6 (Janssen, 2006;Jones et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation